2012
DOI: 10.1097/nen.0b013e31823f2cb0
|View full text |Cite
|
Sign up to set email alerts
|

BRAFAlterations in Primary Glial and Glioneuronal Neoplasms of the Central Nervous System With Identification of 2 Novel KIAA1549

Abstract: Recent studies highlight the importance of BRAF alterations resulting in mitogen activated protein kinase (MAK/ERK) pathway activation in low-grade CNS tumors. We studied 106 low-grade CNS neoplasms in a cohort of primarily pediatric patients to identify the prevalence and clinicopathologic significance of these alterations. Polymerase chain reaction testing identified KIAA1549:BRAF fusions in 51 (48%) tumors overall, including 42 (60%) pilocytic astrocytomas, 4 (17%) unclassifiable low-grade gliomas, 4 (36%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 30 publications
5
119
2
4
Order By: Relevance
“…Gateway cloning (Invitrogen) and site-directed mutagenesis were used to generate the following Myctagged constructs: wild-type BRAF, kinase-dead K482M BRAF mutant (KD), BRAF V600E mutant (V600E), HRASV12 mutant (RASV12), and wild-type KIAA1549. Full-length, "long form" KIAA1549-BRAF fusion (Fusion-1) was generated by translationally silent site-directed mutagenesis, providing restriction sites that permitted the construction of the KIAA1549-BRAF gene fusion via restriction digest/subcloning of the N terminus of KIAA1549 (exons [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Fig. 1F).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gateway cloning (Invitrogen) and site-directed mutagenesis were used to generate the following Myctagged constructs: wild-type BRAF, kinase-dead K482M BRAF mutant (KD), BRAF V600E mutant (V600E), HRASV12 mutant (RASV12), and wild-type KIAA1549. Full-length, "long form" KIAA1549-BRAF fusion (Fusion-1) was generated by translationally silent site-directed mutagenesis, providing restriction sites that permitted the construction of the KIAA1549-BRAF gene fusion via restriction digest/subcloning of the N terminus of KIAA1549 (exons [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Fig. 1F).…”
Section: Methodsmentioning
confidence: 99%
“…The discovery of an oncogenic KIAA1549-BRAF fusion as a hallmark genetic event in pediatric low-grade astrocytomas suggests that recently developed targeted approaches may offer therapeutic opportunities for BRAF-altered tumors (2)(3)(4). The KIAA1549-BRAF fusion gene forms as a result of an internal, nonrandom tandem duplication event in chromosome 7q34 in which the N terminus of the KIAA1549 gene is fused with the C terminus of BRAF, preserving the BRAF kinase domain.…”
Section: Paradoxical Activation and Raf Inhibitor Resistance Of Braf mentioning
confidence: 99%
“…The presence of both alterations has been recently reported for a low-grade astrocytoma. 28 As there is only a single such case, the effect of both alterations on tumor behavior, while curious, is not clear.…”
Section: Modern Pathology (2013) 26 1279-1287mentioning
confidence: 99%
“…The presence of other less common activating alterations in BRAF is one possible explanation for our findings. Among the BRAF fusion products reported in pilocytic astrocytoma, 28 we only tested for KIAA1549:BRAF. This raises the possibility that other alterations in BRAF may drive the activation of p-MAPK1 and CDKN2A in pilocytic astrocytoma of the optic nerve.…”
Section: Modern Pathology (2013) 26 1279-1287mentioning
confidence: 99%
“…However, unlike pilocytic astrocytomas, the rarity and diversity of diffuse PLGGs combined with the scarcity of frozen tissue available for genomic analyses has historically impeded identification of genetic alterations specific to these tumors. Prior studies have found that BRAF-KIAA1549 fusions are rare to nonexistent in diffuse PLGGs, particularly in DA2s (10). Diffuse PLGGs included in large cohorts of low-and high-grade gliomas were suggested to have increased expression of the proto-oncogene v-myb avian myeloblastosis viral oncogene homolog (MYB), including rare cases with genomic aberrations involving the gene (11), but no unifying recurrent genetic events have been identified.…”
mentioning
confidence: 99%